Policy assessment of an EU wide flat area CAP payments system - Erjavec, Emil; Chantreuil, Frédéric; Hanrahan, Kevin; Donnellan, Trevor; Salputra, Guna; Kožar, Maja; van Leeuwen, Myrna (Economic modelling, 2011)
While the evolution of the Common Agricultural Policy (CAP) until 2013 is clear, European Union (EU) budgetary pressures and the perceived unfairness of the distribution of CAP support across Member States has lead to uncertainty over the design of the CAP post 2013. One comprehensive reform option being considered is the implementation of an EU wide flat area payment (EUWFAP) system and a reduction of the total budget available for direct payments. It is hypothesised that the implementation of this policy proposal would lead to significant changes in the distribution of the EU budget and to the redistribution of agricultural production between the Member States, which could hinder the implementation of the proposal. This paper evaluates the rationality of the EUWFAP, based on the analysis of its budgetary and market impacts. Using the AGMEMOD 2020 combined model, the introduction of the EUWFAP in 2013 is compared with a baseline continuation of the current policy. Results suggest that there would be minor negative impacts on the agricultural production at the EU level, but that more substantial impact for some commodities, most notably beef, and could occur in the individual EU Member States. An important outcome of such a policy reform would be a substantial change in the budget allocation between Member States, which could help mitigate the budgetary tensions between the Member States. ► EU wide flat area payments (EUWFAP) could change the EU budget significantly. ► EUWFAP could have minor negative impacts on the agricultural production. ► More substantial impact is for beef. ► The agricultural production in the EU15 would be affected to a greater degree.